Race, ethnicity, and immigration in the 2005 mayoral elections in Los Angeles and New York - John Mollenkopf; Ana Champeny; Raphael Sonenshein; Mark Drayse (University of California, Institute of Urban and Regional Development (IURD), 2007)
Prepared for Panel 30-3, 'Group Mobilization, Partisanship, Ideas, and Leadership: The Los Angeles and New York Mayoral Elections of 2005', September 2, 2006 at the Annual Meeting of the American Political Science Association, Philadelphia
Keywords: 330